Iron Oxide Nanoparticles: Green Synthesis and Their Antimicrobial Activity - Johana Zúñiga-Miranda; Julio Guerra; Alexander Mueller; Arianna Mayorga-Ramos; Saskya E. Carrera-Pacheco; Carlos Barba-Ostria; Jorge Heredia-Moya; Linda P. Guamán (Nanomaterials, 2023)
The rise of antimicrobial resistance caused by inappropriate use of these agents in various settings has become a global health threat. Nanotechnology offers the potential for the synthesis of nanoparticles (NPs) with antimicrobial activity, such as iron oxide nanoparticles (IONPs). The use of IONPs is a promising way to overcome antimicrobial resistance or pathogenicity because of their ability to interact with several biological molecules and to inhibit microbial growth. In this review, we outline the pivotal findings over the past decade concerning methods for the green synthesis of IONPs using bacteria, fungi, plants, and organic waste. Subsequently, we delve into the primary challenges encountered in green synthesis utilizing diverse organisms and organic materials. Furthermore, we compile the most common methods employed for the characterization of these IONPs. To conclude, we highlight the applications of these IONPs as promising antibacterial, antifungal, antiparasitic, and antiviral agents.